The Concentration and Potential of Organic Farming and Processing on the Organic Food Market in Poland - Grzybowska-Brzezińska, Mariola; Grzywińska-Rąpca, Małgorzata; Kuberska , Dominika (Studia Oeconomica Posnaniensia, 2018)
The global organic food market is constantly growing. Poland is in line with this trend; however, relatively high levels of organic food prices are destabilizing the market. One of the conditions of the present decline is the increase in the dynamics of supply accompanied by the standardization of production and spatial concentration. Therefore, the aim of the article is to indicate the spatial diversity of the production of organic farming and processing and to determine their potential. From the conducted analysis, we identified four groups of voivodships by selecting diagnostic features using cluster analysis algorithms. The identified differences between voivodships in the number and arable area of organic farms and the number of organic food processors are not transitory. These disproportions will persist or deepen due to different directions taken by voivodships, especially their policy on rural development and support for organic farming and processing. The deepening spatial concentration on the organic food market should, however, translate into growth in its potential and result in decreasing prices. The condition for such a scenario, however, is to overcome the barrier resulting from the fact that voivodships recording the highest concentration of organic agricultural production and voivodships where the most processors are located are not the same.